Studi Farmakofor Reseptor COX-2 Sebagai Anti Inflamasi - Nursalam Hamzah; Ahmad Najib; Nurshalati Thahir; Ika Misqawati (Jurnal Farmasi UIN Alauddin Makassar, 2014)
Cyclooxygenase (COX) receptor is a dual-function receptor that bound to the membrane which acts to catalyze two important stages in the formation of prostanoide, namely cyclooxigenation and peroxidation. Cyclooxigenation stage is the stage in which COX cyclization process and the addition of two molecules of oxygen to arachidonic acid to form prostaglandin G2 (PGG2). While the stage is the stage of the reduction of the peroxidation of PGG2 endoperoxide become unstable compound called prostaglandine H2 (PGH2). The purpose of this study is to determine the features that are important pharmacophore on anti-inflammatory activity of compounds on COX-2 receptor.  Modeling  and  determination  pharmacophore  features  created  using  the program MOE application version 2009 Virtual screening of chemical compounds to look for natural ingredients in accordance with pharmacophore features that have been made. Molecular docking to study ligand-receptor interactions, performed using MOE.